Opportunities for Audiologists to Use Patient-Centered Communication during Hearing Device Monitoring Encounters - Coleman, Corinne K.; Muñoz, Karen; Ong, Clarissa W.; Butcher, Grayson M.; Nelson, Lauri; Twohig, Michael (Seminars in Hearing, 2018)
Patient-centered care incorporates patient's priorities, values, and goals. Audiologists can increase patient engagement when they use patient-centered principles during communication. Recent research, however, has revealed counseling gaps in audiology that could be detrimental to the intervention process. The present study sought to understand the extent patient-centered communication strategies were used during hearing device monitoring visits by analyzing audio recordings. Counseling portions of the appointments were transcribed using conversation analysis. Missed opportunities were observed, including not validating patients' emotional concerns, providing technical responses to emotional concerns, providing information without determining patient desire for the information, and not engaging the patient in a shared planning process. Training opportunities to enhance audiological services will be discussed.
Keywords: Counseling; audiology; patient-centered care